Automation of Conveyor System Based on Internet of Things (IoT) with Remote Control via Telegram Bot and ESP32 - Selamat Meliala; Yogi Satya; Rosdiana Rosdiana; Taufiq Taufiq; Yasir Amani (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2026)
This study presents the design and implementation of an IoT-based automated conveyor system using the ESP32 microcontroller and Telegram bot for remote control. The system integrates the L298N motor driver to precisely control the speed and direction of a 12V DC motor. Telegram serves as the communication platform, enabling real-time notifications, remote monitoring, and operational control, thereby enhancing user convenience and operational flexibility. The experimental results demonstrate the system's stability across various operating conditions. Testing revealed consistent performance in controlling motor speed and direction without overheating or disruptions, even during extended operations. The system effectively integrates IoT and automation technologies to provide a scalable, cost-effective solution for modern industrial conveyor systems. This research contributes to the advancement of Industry 4.0 by addressing the growing demand for efficient, remote-controlled automation. The proposed system offers significant potential for application in industrial settings, emphasizing reliability, ease of use, and adaptability. Future enhancements could focus on incorporating additional sensors and advanced analytics to improve system intelligence and extend functionality.